2014
DOI: 10.1038/nclimate2370
|View full text |Cite
|
Sign up to set email alerts
|

Feasible mitigation actions in developing countries

Abstract: Abstract'Preventing dangerous anthropogenic climate change' (UNFCCC 1992) will only be feasible with substantial emission reductions below the business--as--usual case in developing countries. Because of the central role of energy for economic development, reducing emissions in developing countries without undermining their development goals requires a fundamental structural break of the historical correlation between economic growth and GHG emissions. While possible in theory, such a transformation of the glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 71 publications
0
45
0
1
Order By: Relevance
“…An incentive for switching to alternative sources of energy could lie in policy objectives other than climate policy, such as those addressing local air pollution, energy security, and energy access (22). In a meta-analysis of air quality cobenefits, Nemet et al (23) found that emission reductions would yield mean health cobenefits of US$49 per ton of CO 2 (tCO 2 ) (with a range of US$2-196 per tCO 2 , the highest cobenefits being seen in developing countries).…”
Section: Discussionmentioning
confidence: 99%
“…An incentive for switching to alternative sources of energy could lie in policy objectives other than climate policy, such as those addressing local air pollution, energy security, and energy access (22). In a meta-analysis of air quality cobenefits, Nemet et al (23) found that emission reductions would yield mean health cobenefits of US$49 per ton of CO 2 (tCO 2 ) (with a range of US$2-196 per tCO 2 , the highest cobenefits being seen in developing countries).…”
Section: Discussionmentioning
confidence: 99%
“…Under Workstream 2, FFSR can contribute significantly to increasing pre-2020 ambition-especially because it is a measure that is ready and available to be deployed today. Jakob et al (2014) point to FFSR, along with decentralized modern energy for rural areas and fuel switching in the energy sector, as one of three feasible mitigation policy instruments to help reach a 2°C target. IEA (2013) points to FFSR as one of the 4-for-2°C policy options for reducing emissions from the energy sector.…”
Section: Consumer Subsidies To Fossil Fuels and Ghg Emissions Reductimentioning
confidence: 99%
“…Existing and future climate flows have been investigated by a number of authors (see Ampri et al, 2014;Bowen, Campiglio, & Tavoni, 2014;Clapp, Ellis, & Corfee-Morlot, 2012;Jakob et al, 2014;Jürgens et al, 2012;Kirkman, Seres, & Haites, 2013;Olbrisch, Haites, Savage, Dadhich, & Shrivastava, 2011). A challenge only very recently addressed has been the lack of a common set of guidelines and definitions to ensure consistency between estimates (World Bank, 2015).…”
Section: The Landscape Of Climate Finance: a Top-down Perspectivementioning
confidence: 99%